2017
DOI: 10.1186/s13019-017-0597-1
|View full text |Cite
|
Sign up to set email alerts
|

Ex-vivo recruitment and x-ray assessment of donor lungs in a challenging retrieval from a donor supported by lvad using the portable normothermic perfusion system: a case report

Abstract: BackgroundLung transplantation (LTx) is limited by the shortage of suitable donors. To overcome this problem, many programs have begun to use donors with extended criteria (marginal donors). However, brain-dead patients with implanted mechanical circulatory support system have rarely been considered as potential lung donors. This case demonstrates the feasibility of lung transplantations from organ donors supported by a mechanical circulatory support system despite the possible difficulties of lung retrieval.C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The number of reports describing organ retrieval from donors with LVADs is still small [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of reports describing organ retrieval from donors with LVADs is still small [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The suitability of patients with LVADs for organ donation has not been addressed in terms of guidelines [1,4]. Considering prior cardiac failure and cardiac surgery, it is a relative contraindication [1][2][3][4][5]. However, after LVAD implantation, all systemic organs could be kept stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Steen Solution -это раствор, содержащий декстран и альбумин, имитирующий концентрации внеклеточных электролитов [8,14,15]. OCS Lung Solution -это аналогичный буферный раствор, содержащий декстран вместо альбумина [5,8,20,21].…”
Section: Discussionunclassified
“…Some more complicated cases, such as donors as brain-dead patients implanted with mechanical circulatory support system or bilateral lungs procured and transplanted after using of portable normothermic perfusion device, reaching the aim of reducing ischemic injury while assessing the marginal donor lungs for suitability [28]. A large and non-randomized trial DEVELOP-UK, showed that 34% untransplantable lung could be put into procedure after EVLP.…”
Section: Effect Of Evlp On Marginal Lungs and More Complicated Casesmentioning
confidence: 99%